TURNOVER INTENTION KARYAWAN: APAKAH KEPEMIMPINAN DAN KOMPENSASI PENYEBABNYA ? (STUDI KASUS PADA CV. ANSOR GROUP KOTAGEDE) DI MASA PANDEMI COVID-19 - Sofiati Sofiati; Aulia Rifany Deslitasari (STKIP PGRI Tulungagung, 2022)
This study aims to test and analyze whether leadership and compenzation affect employee turnover intention at CV Anshor Group Kotagede.The population is 46 employees and a sample of 41 with the sampling technique non probability sampling using the slovin method. The data analysis technique uses multiple regression analysis and hipothesis testing through t test and F testwith SPSS.25.software. The result showed that partially leadership has a negative and significant effect on employee turnover intention . Compensation has a positive but not significant effect on employee turnover intention. Simultaneously leadership and compensation have a positive and significant effect on employee turnover intention.the results of the analysis coefficient determination indicate that employee turnover intention of 44,9% is the influenced by leadership and compensation variables.While the remaining 55.1% is influenced by other factors that are not in this study.For further researchers,it is suggested to develop research using other variables,such as organizational commitment and work environment.